A Framework to Investigate the Effects of Observation Error on Neural Network Predictions of Fish Age - Derek W. Chamberlin; Thomas E. Helser; John D. Brogan; Irina M. Benson; Jason Conner; Andrew T. Chin; Christopher M. Gburski; Mary Elizabeth Matta; Julie A. Pearce; Kali R. Stone; Todd T. TenBrink; Morgan B. Arrington (Fish and Fisheries, 2026)
Technological innovations for predicting fish age represent a paradigm shift from conventional age estimation methods used in fisheries science. Recently developed secondary methods rely on models trained on conventional age estimates, derived from subjective interpretation of growth patterns and a biological property of the fish to predict age. Hence, quantifying the error that propagates from these models and the conventional age estimates on which they are trained is critical to fully account for uncertainty in predicted ages used in fisheries stock assessments. We review the development of three secondary age prediction methods: image analysis, epigenetics and Fourier transform near‐infrared spectroscopy (FT‐NIRS); the use of artificial intelligence (AI) within each method; and present an approach to examine the effects of ageing error on AI age prediction models. As a case study, we conducted an empirical study, coupled with simulation, to quantify the effects of ageing error on the performance of a multimodal convolutional neural network (MMCNN) model used to predict eastern Bering Sea walleye pollock ( Gadus chalcogrammus ) ages from otoliths analysed using FT‐NIRS. Results indicated repeatability of predicted ages was high between instrument operators, while adding ageing error resulted in a slight decrease in model performance from R 2 = 0.92 and CV = 7.6% to R 2 = 0.87 and CV = 10.2% on test datasets. Our results also suggest the MMCNN model is robust to noise in calibration age data and model performance may be better than performance metrics indicate when the model is evaluated against data with increased error.

Health Outcomes Following Traumatic Brain Injury: An Umbrella Review - Jason M. Toliao; Junhyuk Lee; Hans Oh; San Lee; Lucas Conner; Stefan Blüml; Peter A. Chiarelli; Pradip P. Chaudhari (Neuropsychology Review, 2026)
An increasing number of systematic reviews and meta-analyses examine health outcomes from traumatic brain injury (TBI). This umbrella review examines the association of TBI with comorbid health outcomes and evaluates the methodological rigor of existing literature. This protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO; Registration No. CRD42024581341). EMBASE, PubMed, MEDLINE, and the Cochrane Library were searched from database inception to November 26, 2025. Two reviewers screened abstracts and full texts using predefined criteria. Meta-analyses of observational studies were included if they assessed health outcomes following TBI and reported effect sizes were convertible to pooled equivalent odds ratios (eOR). PRISMA (Preferred Reporting Items of Systematic Reviews and Meta-Analyses) guidelines were utilized for study formatting. We applied AMSTAR2 (A Measurement Tool to Assess Systematic Reviews 2) criteria to assess the quality of included studies. Health outcomes described in each meta-analysis were reanalyzed and presented through eOR using a random-effects model. 41 meta-analyses were included, covering 671 original studies and 53 comorbid health outcomes, in a cohort comprising 83 million participants across 40 countries. Our findings suggest that traumatic brain injury, acquired at any age, may be associated with impairments across neurological, somnological, cognitive, mental health, and behavioral domains. Despite these associations, 78% of the included studies were themselves classified as having “critically low” methodological quality by AMSTAR2 criteria, which limited the ability to provide causal conclusions. These findings may help inform care guidelines following TBI. Improved research frameworks are important to better understand the lasting effects of TBI.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Corrigendum to “Loss of c-Met signaling sensitizes hepatocytes to lipotoxicity and induces cholestatic liver damage by aggravating oxidative stress” [Toxicology 361–362 (2016) 39–48] - Luis E. Gomez-Quiroz; Daekwan Seo; Yun-Han Lee; Mitsuteru Kitade; Timo Gaiser; Matthew Gillen; Seung-Bum Lee; Ma Concepcion Gutierrez-Ruiz; Elizabeth A. Conner; Valentina M. Factor; Snorri S. Thorgeirsson; Jens U. Marquardt (Toxicology, 2026)

Biogeography and Anthropogenic Development Shape Mesopredator Distributions in a Rapidly Developing Region - Alex D. Potash; L. Mike Conner; Marcus Lashley; Michael Cherry; Andrew J. Edelman; Elina Garrison; Daniel U. Greene; William Gulsby; Matthew T. Hallett; David S. Jachowski; Paul Taillie; Robert A. McCleery (Journal of Biogeography, 2026)
Aim To investigate effects of anthropogenic development at regional and landscape scales on the distributions of mid‐trophic level mammalian predators (mesopredators) across the southeastern United States. Location The study area encompasses seven ecoregions across a large portion of the southeastern United States. Taxon Mammalian mesopredators. Methods We compiled trail camera data from 21 studies across the southeastern United States and used occupancy modelling to assess mesopredator distributions and account for heterogeneous detection probabilities. We examined drivers of occupancy at regional and landscape scales. At the regional scale, we assessed occupancy patterns across ecoregions differing in topography, productivity, and human population growth. At the landscape scale, we analysed the influence of land cover types (forest, developed, agriculture) and non‐native coyote ( Canis latrans ) activity on occupancy. Results Regionally, mesopredator occurrence was highest in ecoregions characterised by low productivity and greater topographic variability. Common species (predicted occupancy ≥ 0.19) showed positive associations with developed and agricultural land covers, while less common species (predicted occupancy ≤ 0.10) showed negative associations or were too rare to model. Coyote activity had mixed effects, positively associated with some species while negatively associated with others. Main Conclusions Anthropogenic development affects mesopredator communities at both regional and landscape scales, favouring generalist species that are tolerant of human‐modified landscapes.

Forest Community Structure and Aboveground Net Primary Productivity across an Elevation Gradient in the Congaree River floodplain, South Carolina, USA - Jamie A. Duberstein; Gavin Blosser; William H. Conner (Wetlands, 2025)
Forested wetlands provide a valuable potential sink for atmospheric carbon, with rates varying between tree communities. Previous studies found that topographic position within the Congaree Swamp (South Carolina, USA) influences flooding regimes, sedimentation processes, and forest community types. We measured aboveground net primary productivity (ANPP) for four distinct tree community types situated within an elevational gradient of this floodplain forest. Twenty data collection sites, blocked by a priori elevational differences, were established along five roughly parallel transects with four 20 × 25-m plots along each transect. Total ANPP was estimated using the sum of annual litterfall (five 0.25 m 2 litter traps/plot) and annual incremental increase in tree biomass. Tree (stems ≥ 10 cm diameter) wood ANPP ranged from 409 to 606 g/m 2 while total litterfall ranged from 678 to 705 g/m 2 . Total ANPP, tree wood biomass, and biomass of reproductive materials (mast) varied annually but sapling biomass, leaf litter, and total litterfall did not. Total and fractional ANPP differed between some forest community types with lowest and highest rates measured in communities occupying high floodplain elevation sites. The community occupying low elevation sites had the lowest rates of total ANPP but highest litter production. The community occupying intermediate floodplain elevation sites had the second highest rates for total, and most measured fractions, of ANPP. Sapling (stems < 10 cm diameter) wood averaged 5.8% of total ANPP for one community, suggesting that, in areas with a moderate to dense sapling layer, sapling wood is an important component of ANPP.

Preliminary investigation of planar Sun-Ceres trajectories in variable restricted dynamical models - Robert A. Bettinger; Elliot A. Potter; Conner S. O’Malley; Annika J. Gilliam; Tyler J. Kapolka (Advances in Space Research, 2025)

Correction to: White matter lipid alterations during aging in the rhesus monkey brain - Christina Dimovasili; Ana T. Vitantonio; Bryce Conner; Kelli L. Vaughan; Julie A. Mattison; Douglas L. Rosene (GeroScience, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Maximizing biological insights from instruments attached to animals - Roxanne S. Beltran; A. Marm Kilpatrick; Simona Picardi; Briana Abrahms; Gabriel M. Barrile; William K. Oestreich; Justine A. Smith; Max F. Czapanskiy; Arina B. Favilla; Ryan R. Reisinger; Jessica M. Kendall-Bar; Allison R. Payne; et al. (Trends in Ecology & Evolution, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Long‐term studies should provide structure for inclusive education and professional development - Max F. Czapanskiy; Lina M. Arcila Hernández; Cara Munro; Isabella Garfield; Adrien Bastidas; Allison R. Payne; Kelli Ong; Natalie A. Storm; Taiki Adachi; Conner M. Hale; Astarte Brown; Patrick W. Robinson; et al. (Ecology Letters, 2024)
Long‐term studies are critical for ecological understanding, but they are underutilized as inclusive opportunities for training ecologists. We use our perspective from the Año Nuevo elephant seal programme along with surveys from community members to propose that long‐term studies could be better leveraged to promote inclusive education and professional development in ecology. Drawing on our experiences as mentors and mentees, we demonstrate how long‐term studies can use their resources, including rich data , robust logistics and extensive professional networks , to improve recruitment and retention of diverse groups of trainees. However, practices such as unpaid labour and unclear expectations limit the utility of these resources for diversifying ecology. We discuss how we have structured our long‐term study to create more inclusive and equitable training opportunities. Acknowledging these transformations required substantial resources, we highlight funding sources and organizational partnerships that can promote investment in long‐term studies for broadening participation.

Correction: Presence of Hummock and Hollow Microtopography Reflects Shifting Balances of Shallow Subsidence and Root Zone Expansion Along Forested Wetland River Gradients - Ken W. Krauss; Gregory B. Noe; Jamie A. Duberstein; Nicole Cormier; Andrew S. From; Thomas R. Doody; William H. Conner; Donald R. Cahoon; Darren J. Johnson (Estuaries and Coasts, 2024)

Presence of Hummock and Hollow Microtopography Reflects Shifting Balances of Shallow Subsidence and Root Zone Expansion Along Forested Wetland River Gradients - Ken W. Krauss; Gregory B. Noe; Jamie A. Duberstein; Nicole Cormier; Andrew S. From; Thomas R. Doody; William H. Conner; Donald R. Cahoon; Darren J. Johnson (Estuaries and Coasts, 2024)

Ex vivo and in vitro methods as a platform for studying anthropogenic effects on marine mammals: four challenges and how to meet them - Juan Manuel Vazquez; Jane I. Khudyakov; Carla B. Madelaire; Céline A. Godard-Codding; Heli Routti; Emily K. Lam; Elizabeth R. Piotrowski; Greg B. Merrill; Jillian H. Wisse; Kaitlin N. Allen; Justin Conner; Pierre Blévin; et al. (Frontiers in Marine Science, 2024)
Marine mammals are integral to global biodiversity and marine health through their roles in coastal, benthic, and pelagic ecosystems. Marine mammals face escalating threats from climate change, pollution, and human activities, which perturb their oceanic environment. The diverse biology and extreme adaptations evolved by marine mammals make them important study subjects for understanding anthropogenic pressures on marine ecosystems. However, ethical and logistical constraints restrict the tractability of experimental research with live marine mammals. Additionally, studies on the effects of changing ocean environments are further complicated by intricate gene-environment interactions across populations and species. These obstacles can be overcome with a comprehensive strategy that involves a systems-level approach integrating genotype to phenotype using rigorously defined experimental conditions in vitro and ex vivo . A thorough analysis of the interactions between the genetics of marine mammals and their exposure to anthropogenic pressures will enable robust predictions about how global environmental changes will affect their health and populations. In this perspective, we discuss four challenges of implementing such non-invasive approaches across scientific fields and international borders: 1) practical and ethical limitations of in vivo experimentation with marine mammals, 2) accessibility to relevant tissue samples and cell cultures; 3) open access to harmonized methods and datasets and 4) ethical and equitable research practices. Successful implementation of the proposed approach has the potential impact to inspire new solutions and strategies for marine conservation.

Genetic support for discrete conservation units of the fossorial rodent Geomys pinetis - Sarah I. Duncan; Robert A. McCleery; Celine M. Carneiro; J. T. Pynne; Elizabeth I. Parsons; L. Mike Conner; Steven B. Castleberry; Robert A. Gitzen; James D. Austin (Conservation Genetics, 2024)

White matter lipid alterations during aging in the rhesus monkey brain - Christina Dimovasili; Ana T. Vitantonio; Bryce Conner; Kelli L. Vaughan; Julie A. Mattison; Douglas L. Rosene (GeroScience, 2024)

Constraining sulfur incorporation in calcite using inorganic precipitation experiments - Szabina Karancz; Joji Uchikawa; Lennart J. de Nooijer; Mariëtte Wolthers; Kyle A. Conner; Corinne G. Hite; Richard E. Zeebe; Shiv K. Sharma; Gert-Jan Reichart (Geochimica et Cosmochimica Acta, 2024)

Effect of fast charging on degradation and safety characteristics of lithium-ion batteries with LiNi Co Mn Al1---O2 cathodes - Hanwei Zhou; Anuththara S. Alujjage; Maria Terese; Conner Fear; Tapesh Joshi; Vallabha Rao Rikka; Judith A. Jeevarajan; Partha P. Mukherjee (Chemical Engineering Journal, 2024)

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Immune proteins C1q and CD47 may contribute to aberrant microglia-mediated synapse loss in the aging monkey brain that is associated with cognitive impairment - Sarah A. DeVries; Bryce Conner; Christina Dimovasili; Tara L. Moore; Maria Medalla; Farzad Mortazavi; Douglas L. Rosene (GeroScience, 2023)

Increased sea ice melt as a driver of enhanced Arctic phytoplankton blooming - Andrew P. Castagno; Till J. W. Wagner; Mattias R. Cape; Conner W. Lester; Elizabeth Bailey; Catharina Alves‐de‐Souza; Robert A. York; Alyson H. Fleming (Global Change Biology, 2023)
Phytoplankton primary production in the Arctic Ocean has been increasing over the last two decades. In 2019, a record spring bloom occurred in Fram Strait, characterized by a peak in chlorophyll that was reached weeks earlier than in other years and was larger than any previously recorded May bloom. Here, we consider the conditions that led to this event and examine drivers of spring phytoplankton blooms in Fram Strait using in situ, remote sensing, and data assimilation methods. From samples collected during the May 2019 bloom, we observe a direct relationship between sea ice meltwater in the upper water column and chlorophyll a pigment concentrations. We place the 2019 spring dynamics in context of the past 20 years, a period marked by rapid change in climatic conditions. Our findings suggest that increased advection of sea ice into the region and warmer surface temperatures led to a rise in meltwater input and stronger near‐surface stratification. Over this time period, we identify large‐scale spatial correlations in Fram Strait between increased chlorophyll a concentrations and increased freshwater flux from sea ice melt.

145 4-H does more than show to grow: Rebuilding educational opportunities and emphasizing positive youth development in a previously show-only focused program - K. Irvine; C. Wickens; A. Schortinghouse; S. Conner (Journal of Equine Veterinary Science, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Synthetic Microfiber Material Influences Ingestion by Freshwater Worms - Sarah A. Martinez; Conner J. Simon; Risa A. Cohen (Bulletin of Environmental Contamination and Toxicology, 2023)

Associations of household factors, hot water temperature, and chlorine residual with Legionella occurrence in single-family homes in New Jersey - Jessie A. Gleason; Lauren E. Conner; Kathleen M. Ross (Science of The Total Environment, 2023)

Unpacking the Role of Extracellular Vesicles in Ischemic and Hemorrhagic Stroke: Pathophysiology and Therapeutic Implications - Yonatan Hirsch; Joseph R. Geraghty; Cory R. Reiter; Eitan A. Katz; Conner F. Little; Matthew K. Tobin; Fernando D. Testai (Translational Stroke Research, 2023)

Prey species increase activity in refugia free of terrestrial predators - Alex D. Potash; L. Mike Conner; Michael Clinchy; Liana Y. Zanette; Robert A. McCleery (Oecologia, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Gene activation via Cre/lox-mediated excision in cowpea (Vigna unguiculata) - Zhifen Zhang; Yinping Guo; Kathleen Monfero Marasigan; Joann A. Conner; Peggy Ozias-Akins (Plant Cell Reports, 2022)
Key message Expression of Cre recombinase by AtRps5a pro or AtDD45 pro enabled Cre/ lox -mediated recombination at an early embryonic developmental stage upon crossing, activating transgenes in the hybrid cowpea and tobacco. Abstract Genetic engineering ideally results in precise spatiotemporal control of transgene expression. To activate transgenes exclusively in a hybrid upon fertilization, we evaluated a Cre/ lox -mediated gene activation system with the Cre recombinase expressed by either AtRps5a or AtDD45 promoters that showed activity in egg cells and young embryos. In crosses between Cre recombinase lines and transgenic lines harboring a lox -excision reporter cassette with ZsGreen driven by the AtUbq3 promoter after Cre/ lox -mediated recombination, we observed complete excision of the lox -flanked intervening DNA sequence between the AtUbq3 pro and the ZsGreen coding sequence in F 1 progeny upon genotyping but no ZsGreen expression in F 1 seeds or seedlings. The incapability to observe ZsGreen fluorescence was attributed to the activity of the AtUbq3 pro . Strong ZsGreen expression in F 1 seeds was observed after recombination when ZsGreen was driven by the AtUbq10 promoter. Using the AtDD45 pro to express Cre resulted in more variation in recombination frequencies between transgenic lines and crosses. Regardless of the promoter used to regulate Cre , mosaic F 1 progeny were rare, suggesting gene activation at an early embryo-developmental stage. Observation of ZsGreen -expressing tobacco embryos at the globular stage from crosses with the AtRps5a pro Cre lines pollinated by the AtUbq3 pro lox line supported the early activation mode.

Prey tells, large herbivores fear the human ‘super predator’ - Daniel A. Crawford; L. Mike Conner; Michael Clinchy; Liana Y. Zanette; Michael J. Cherry (Oecologia, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Does Ankle Exoskeleton Assistance Impair Stability During Walking in Individuals with Cerebral Palsy? - Taryn A. Harvey; Benjamin C. Conner; Zachary F. Lerner (Annals of Biomedical Engineering, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Are we ready to track climate‐driven shifts in marine species across international boundaries? ‐ A global survey of scientific bottom trawl data - Aurore A. Maureaud; Romain Frelat; Laurène Pécuchet; Nancy Shackell; Bastien Mérigot; Malin L. Pinsky; Kofi Amador; Sean C. Anderson; Alexander Arkhipkin; Arnaud Auber; Iça Barri; Richard J. Bell; et al. (Global Change Biology, 2021)
Marine biota are redistributing at a rapid pace in response to climate change and shifting seascapes. While changes in fish populations and community structure threaten the sustainability of fisheries, our capacity to adapt by tracking and projecting marine species remains a challenge due to data discontinuities in biological observations, lack of data availability, and mismatch between data and real species distributions. To assess the extent of this challenge, we review the global status and accessibility of ongoing scientific bottom trawl surveys. In total, we gathered metadata for 283,925 samples from 95 surveys conducted regularly from 2001 to 2019. We identified that 59% of the metadata collected are not publicly available, highlighting that the availability of data is the most important challenge to assess species redistributions under global climate change. Given that the primary purpose of surveys is to provide independent data to inform stock assessment of commercially important populations, we further highlight that single surveys do not cover the full range of the main commercial demersal fish species. An average of 18 surveys is needed to cover at least 50% of species ranges, demonstrating the importance of combining multiple surveys to evaluate species range shifts. We assess the potential for combining surveys to track transboundary species redistributions and show that differences in sampling schemes and inconsistency in sampling can be overcome with spatio‐temporal modeling to follow species density redistributions. In light of our global assessment, we establish a framework for improving the management and conservation of transboundary and migrating marine demersal species. We provide directions to improve data availability and encourage countries to share survey data, to assess species vulnerabilities, and to support management adaptation in a time of climate‐driven ocean changes.

Salinity, Water Level, and Forest Structure Contribute to Baldcypress (Taxodium distichum) Rhizosphere and Endosphere Community Structure - Candice Y. Lumibao; Elizabeth Kimbrough; Stephen Formel; Richard H. Day; Andrew S. From; William H. Conner; Ken W. Krauss; Sunshine A. Van Bael (Wetlands, 2020)

Sequencing of Tuta absoluta genome to develop SNP genotyping assays for species identification - Christine A. Tabuloc; Kyle M. Lewald; William R. Conner; Yoosook Lee; Ernest K. Lee; Alexander B. Cain; Kristine E. Godfrey; Judit Arnó; Nuria Agustí; Clerison R. Perini; Jerson C. Guedes; Frank G. Zalom; et al. (Journal of Pest Science, 2019)

Energy-Rich Mesopelagic Fishes Revealed as a Critical Prey Resource for a Deep-Diving Predator Using Quantitative Fatty Acid Signature Analysis - Chandra Goetsch; Melinda G. Conners; Suzanne M. Budge; Yoko Mitani; William A. Walker; Jeffrey F. Bromaghin; Samantha E. Simmons; Colleen Reichmuth; Daniel P. Costa (Frontiers in Marine Science, 2018)

Fisheries Exploitation by Albatross Quantified With Lipid Analysis - Melinda G. Conners; Chandra Goetsch; Suzanne M. Budge; William A. Walker; Yoko Mitani; Daniel P. Costa; Scott A. Shaffer (Frontiers in Marine Science, 2018)

Earlier snowmelt accompanied by warmer soil temperatures in mid-latitude aspen forest and subalpine meadow: Implications for soil carbon - Lafe G. Conner; Richard A. Gill; Joshua T. Harvey (Plant and Soil, 2017)

Quantifying nonadditive selection caused by indirect ecological effects: Reply - Casey P. terHorst; Jennifer A. Lau; Jeffrey K. Conner (Ecology, 2017)

Haploid embryo production in rice and maize induced by PsASGR-BBML transgenes - Joann A. Conner; Maricel Podio; Peggy Ozias-Akins (Plant Reproduction, 2017)

Individual-level Variation and Higher-level Interpretations of Space Use in Wide-ranging Species: An Albatross Case Study of Sampling Effects - Sarah E. Gutowsky; Marty L. Leonard; Melinda G. Conners; Scott A. Shaffer; Ian D. Jonsen (Frontiers in Marine Science, 2015)

Quantifying nonadditive selection caused by indirect ecological effects - Casey P. terHorst; Jennifer A. Lau; Idelle A. Cooper; Kane R. Keller; Raffica J. La Rosa; Anne M. Royer; Elizabeth H. Schultheis; Tomomi Suwa; Jeffrey K. Conner (Ecology, 2015)
In natural biological communities, species interact with many other species. Multiple species interactions can lead to indirect ecological effects that have important fitness consequences and can cause nonadditive patterns of natural selection. Given that indirect ecological effects are common in nature, nonadditive selection may also be quite common. As a result, quantifying nonadditive selection resulting from indirect ecological effects may be critical for understanding adaptation in natural communities composed of many interacting species. We describe how to quantify the relative strength of nonadditive selection resulting from indirect ecological effects compared to the strength of pairwise selection. We develop a clear method for testing for nonadditive selection caused by indirect ecological effects and consider how it might affect adaptation in multispecies communities. We use two case studies to illustrate how our method can be applied to empirical data sets. Our results suggest that nonadditive selection caused by indirect ecological effects may be common in nature. Our hope is that trait‐based approaches, combined with multifactorial experiments, will result in more estimates of nonadditive selection that reveal the relative importance of indirect ecological effects for evolution in a community context.

Occurrence of shallow cold flows in the winter atmospheric boundary layer of interior of Alaska - Gilberto J. Fochesatto; John A. Mayfield; Derek P. Starkenburg; Matthew A. Gruber; James Conner (Meteorology and Atmospheric Physics, 2015)

Southern toads alter their behavior in response to red-imported fire ants - Andrea K. Long; Daniel D. Knapp; Lauren Mccullough; Lora L. Smith; L. Mike Conner; Robert A. Mccleery (Biological Invasions, 2015)

International Guidelines for Bioequivalence of Locally Acting Orally Inhaled Drug Products: Similarities and Differences - Dongmei Lu; Sau L. Lee; Robert A. Lionberger; Stephanie Choi; Wallace Adams; Hoainhon N. Caramenico; Badrul A. Chowdhury; Dale P. Conner; Rohit Katial; Susan Limb; John R. Peters; Lawrence Yu; et al. (The AAPS Journal, 2015)

Abundance and phenology patterns of two pond-breeding salamanders determine species interactions in natural populations - Thomas L. Anderson; Daniel J. Hocking; Christopher A. Conner; Julia E. Earl; Elizabeth B. Harper; Michael S. Osbourn; William E. Peterman; Tracy A. G. Rittenhouse; Raymond D. Semlitsch (Oecologia, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

Impacts of Changing Hydrology and Hurricanes on Forest Structure and Growth Along a Flooding/Elevation Gradient in a South Louisiana Forested Wetland from 1986 to 2009 - William H. Conner; Jamie A. Duberstein; John W. Day; Stephen Hutchinson (Wetlands, 2014)

Value Driven Innovation in Medical Device Design: A Process for Balancing Stakeholder Voices - F. J. de Ana; K. A. Umstead; G. J. Phillips; C. P. Conner (Annals of Biomedical Engineering, 2013)

Recombination within the apospory specific genomic region leads to the uncoupling of apomixis components in Cenchrus ciliaris - Joann A. Conner; Gunawati Gunawan; Peggy Ozias-Akins (Planta, 2013)

Do Hummocks Provide a Physiological Advantage to Even the Most Flood Tolerant of Tidal Freshwater Trees? - Jamie A. Duberstein; Ken W. Krauss; William H. Conner; William C. Bridges; Victor B. Shelburne (Wetlands, 2013)

Implementation of a Reference-Scaled Average Bioequivalence Approach for Highly Variable Generic Drug Products by the US Food and Drug Administration - Barbara M. Davit; Mei-Ling Chen; Dale P. Conner; Sam H. Haidar; Stephanie Kim; Christina H. Lee; Robert A. Lionberger; Fairouz T. Makhlouf; Patrick E. Nwakama; Devvrat T. Patel; Donald J. Schuirmann; Lawrence X. Yu (The AAPS Journal, 2012)

Effect of intravenous vitamin C on cytokine activation and oxidative stress in end-stage renal disease patients receiving intravenous iron sucrose - Todd A. Conner; Charles McQuade; Jonathan Olp; Amy Barton Pai (BioMetals, 2012)

Common Deficiencies with Bioequivalence Submissions in Abbreviated New Drug Applications Assessed by FDA - Qing Liu; Barbara M. Davit; Svetlana A. Cherstniakova; Suman Dandamudi; Johnetta F. Walters; Christina H. Lee; Kimberly W. Raines; Ke Ren; Leeh N. Williamson; Dale P. Conner (The AAPS Journal, 2012)

Effects of prescribed fire, supplemental feeding, and mammalian predator exclusion on hispid cotton rat populations - Gail Morris; Jeffrey A. Hostetler; L. Mike Conner; Madan K. Oli (Oecologia, 2011)

Erratum to: In Vitro Considerations to Support Bioequivalence of Locally Acting Drugs in Dry Powder Inhalers for Lung Diseases - S. L. Lee; W. P. Adams; B. V. Li; D. P. Conner; B. A. Chowdhury; L. X. Yu (The AAPS Journal, 2011)

In Vitro Considerations to Support Bioequivalence of Locally Acting Drugs in Dry Powder Inhalers for Lung Diseases - Sau Lawrence Lee; Wallace P. Adams; Bing V. Li; Dale P. Conner; Badrul A. Chowdhury; Lawrence X. Yu (The AAPS Journal, 2009)

Genetic mapping of the apospory-specific genomic region in Pennisetum squamulatum using retrotransposon-based molecular markers - Heqiang Huo; Joann A. Conner; Peggy Ozias-Akins (Theoretical and Applied Genetics, 2009)

Site condition, structure, and growth of baldcypress along tidal/non-tidal salinity gradients - Ken W. Krauss; Jamie A. Duberstein; Thomas W. Doyle; William H. Conner; Richard H. Day; L. Wayne Inabinette; Julie L. Whitbeck (Wetlands, 2009)

Efficient isolation, culture and regeneration of Lotus corniculatus protoplasts - S. V. Raikar; R. H. Braun; C. Bryant; A. J. Conner; M. C. Christey (Plant Biotechnology Reports, 2008)

Movement and habitat use of two aquatic turtles (Graptemys geographica and Trachemys scripta) in an urban landscape - Travis J. Ryan; Christopher A. Conner; Brooke A. Douthitt; Sean C. Sterrett; Carmen M. Salsbury (Urban Ecosystems, 2008)

Whole genome amplification from plant cell colonies of somatic hybrids using strand displacement amplification - S. V. Raikar; C. Bryant; R. Braun; A. J. Conner; M. C. Christey (Plant Biotechnology Reports, 2007)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Breeding for success: diversity in action - A. J. Conner; C. F. Mercer (Euphytica, 2007)

Intragenic vectors for gene transfer without foreign DNA - Anthony J. Conner; Philippa J. Barrell; Samantha J. Baldwin; Annemarie S. Lokerse; Pauline A. Cooper; Astrid K. Erasmuson; Jan-Peter Nap; Jeanne M. E. Jacobs (Euphytica, 2007)

Assessment of yield loss caused by mycosphaerella blight in field pea crops in western Canada - H. Su; S. F. Hwang; K. F. Chang; R. L. Conner; A. G. Xue; T. D. Warkentin; S. F. Blade; G. D. Turnbull (Journal of Plant Diseases and Protection, 2006)

Geographic patterns in the demersal ichthyofauna of the Aleutian Islands - E. A. LOGERWELL; K. AYDIN; S. BARBEAUX; E. BROWN; M. E. CONNERS; S. LOWE; J. W. ORR; I. ORTIZ; R. REUTER; P. SPENCER (Fisheries Oceanography, 2005)
The goals of this research were to investigate geographic patterns in the Aleutian Island region's demersal ichthyofauna and to determine whether they reflected the physical and biological oceanographic patterns documented by other authors in this volume. The analyses were structured according to the level of organization: at the community level, patterns in species occurrence and community structure were investigated; at the population level, distribution and abundance were examined; at the individual level, food habits and growth were studied. There were step‐changes in species occurrence, diversity, population distribution and food habits at Samalga Pass and at sites farther west. These longitudinal trends indicated physical and biological variation along the length of the Aleutian Islands chain; however, depth‐related patterns were as common as longitudinal patterns in demersal fish distribution. In addition, high catches of patchily distributed species occurred in areas expected to be biological ‘hot spots’ because of increased productivity and prey availability. These patterns suggest linkages between demersal fish ecology and the biophysical processes described by other authors in this volume and indicate that inter‐disciplinary research is needed to elucidate the underlying mechanisms.

Microbial communities of Solanum tuberosum and magainin-producing transgenic lines - M. O’Callaghan; E. M. Gerard; N. W. Waipara; S. D. Young; T. R. Glare; P. J. Barrell; A. J. Conner (Plant and Soil, 2005)

Promising genetic resources for resistance to wheat streak mosaic virus and the wheat curl mite in wheat-Thinopyrum partial amphiploids and their derivatives - Hongjie Li; Robert L. Conner; Qin Chen; Robert J. Graf; André Laroche; F. Ahmad; A. D. Kuzyk (Genetic Resources and Crop Evolution, 2005)

Evolution of plant resistance and tolerance to frost damage - Anurag A. Agrawal; Jeffrey K. Conner; John R. Stinchcombe (Ecology Letters, 2004)
Plant defence against any type of stress may involve resistance (traits that reduce damage) or tolerance (traits that reduce the negative fitness impacts of damage). These two strategies have been proposed as redundant evolutionary alternatives. A late‐season frost enabled us to estimate natural selection and genetic constraints on the evolution of frost resistance and tolerance in a wild plant species. We employed a genetic selection analysis (which is unbiased by environmental correlations between traits and fitness) on 75 paternal half‐sibling families of annual wild radish [ Raphanus raphanistrum (Brassicaceae)]. In an experimental population in southern Ontario, we found strong selection favouring plant resistance to frost, but selection against tolerance to frost. The selection against tolerance may have been caused by a cost of tolerance, as we provide evidence for a negative genetic correlation between tolerance and fitness in the absence of frost damage. Although we found no evidence for the theoretically predicted trade‐off between frost tolerance and resistance among our families, we did detect negative correlational selection acting on the two traits, indicating that natural selection favoured high resistance combined with low tolerance and low resistance coupled with high tolerance, but not high or low levels of both traits together. There were few genetic correlations between the measured traits overall, but frost tolerance was negatively correlated with initial seed mass, and frost resistance was positively correlated with resistance to insect herbivory. Periodic episodes of strong selection such as that caused by the late‐season frost may be disproportionately important in evolution, and are likely becoming more common because of human alterations of the environment.

Transcriptional analysis of dynamic heat-shock response by the hyperthermophilic bacterium Thermotoga maritima - Marybeth A. Pysz; Keith R. Shockley; Clemente I. Montero; Shannon B. Conners; Matthew R. Johnson; Robert M. Kelly; Donald E. Ward (Extremophiles, 2004)

CHARACTERIZATION OF THE HUMAN HEPATOCELLULAR CARCINOMA (HEPG2) CELL LINE AS AN IN VITRO MODEL FOR CADMIUM TOXICITY STUDIES - P. F. DEHN; C. M. WHITE; D. E. CONNERS; G. SHIPKEY; T. A. CUMBO (In Vitro Cellular & Developmental Biology - Animal, 2004)

Characterisation of Triticum vavilovii-derived stripe rust resistance using genetic, cytogenetic and molecular analyses and its marker-assisted selection - H. S. Bariana; G. N. Brown; N. U. Ahmed; S. Khatkar; R. L. Conner; C. R. Wellings; S. Haley; P. J. Sharp; A. Laroche (Theoretical and Applied Genetics, 2002)

Prediction of sample size to maintain genetic variation in doubled-haploid populations following marker selection - A. W. Campbell; P. J. Campbell; W. B. Griffin; D. J. Burritt; A. J. Conner (Theoretical and Applied Genetics, 2001)

Characterization of wheat-Thinopyrum partial amphiploids for resistance to barley yellow dwarf virus - G. Fedak; Q. Chen; R.L. Conner; A. Laroche; A. Comeau; C.A. St.-Pierre (Euphytica, 2001)

Molecular cytogenetic evidence for a high level of chromosome pairing among different genomes in Triticum aestivum–Thinopyrum intermedium hybrids - Q. Chen; R. L. Conner; A. Laroche; F. Ahmad (Theoretical and Applied Genetics, 2001)

Assessment and Modelling of the Environmental Chemistry and Potential for Remediative Treatment of Chromium-Contaminated Land - J.G. Farmer; M.C. Graham; R.P. Thomas; C. Licona-Manzur; C. Licona-Manzur; E. Paterson; C.D. Campbell; J.S. Geelhoed; D.G. Lumsdon; J.C.L. Meeussen; M.J. Roe; A. Conner; et al. (Environmental Geochemistry and Health, 1999)

Molecular characterization of the genome composition of partial amphiploids derived from Triticum aestivum×Thinopyrum ponticum and T. aestivum×Th. intermedium as sources of resistance to wheat streak mosaic virus and its vector, Aceria tosichella - Q. Chen; R. L. Conner; F. Ahmad; A. Laroche; G. Fedak; J. B. Thomas (Theoretical and Applied Genetics, 1998)

Molecular cytogenetic characterization of Thinopyrum intermedium-derived wheat germplasm specifying resistance to wheat streak mosaic virus - Q. Chen; B. Friebe; R. L. Conner; A. Laroche; J. B. Thomas; B. S. Gill (Theoretical and Applied Genetics, 1998)

New Criteria for the Identification of Animal Fats Preserved in Archaeological Pottery - R. P. Evershed; H. R. Mottram; S. N. Dudd; S. Charters; A. W. Stott; G. J. Lawrence; A. M. Gibson; A. Conner; P. W. Blinkhorn; V. Reeves (The Science of Nature, 1997)

A garden study of the effects of ultraviolet-B radiation on pollination success and lifetime female fitness in Brassica - Jeffrey K. Conner; Laura A. Zangori (Oecologia, 1997)